Description of the mature larva of Gastrophysa janthina (Suffrian, 1851) [=G. unicolor auct.] (Coleoptera: Chrysomelidae: Chrysomelinae) and key to the larvae of the European Gastrophysa - Baselga, Andrés (Zootaxa, 2007)
Mature larva of Gastrophysa janthina (Suffrian, 1851) (= G. unicolor auct.) is described and illustrated for the first time, based on specimens collected on Rumex spp. (Polygonaceae) in Spain. Nomenclature of this species is discussed, justifying the use of G. janthina instead of G. unicolor auct. Diagnostic characters for the identification of species within Gastrophysa Chevrolat, 1837 are coloration of dorsal tegument and shape of labrum. This latter character is the only one separating the larva of G. janthina from that of G. viridula (De Geer, 1775). A key to European larvae of genus Gastrophysa is provided. Notes on distribution and host plants are included.